2021
DOI: 10.1177/23094990211020366
|View full text |Cite
|
Sign up to set email alerts
|

No differences in clinical outcomes and cartilage repair between opening wedge and closed wedge high tibial osteotomies at short-term follow-up: A retrospective case series analysis

Abstract: Purpose: The aim of this study was to assess differences in clinical outcomes and postoperative cartilage repair between opening wedge high tibial osteotomy (OWHTO) and closed wedge HTO (CWHTO) for medial osteoarthritis (OA) of the knee. Methods: A total of 90 knees of 76 patients who underwent OWHTO (45 knees of 40 patients) and CWHTO (45 knees of 36 patients) was followed-up for 2 years. Cartilage repair at the medial compartment was arthroscopically classified into the following stages: Stage 1 (no reparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Several authors have reported better macroscopic cartilage regeneration and improved clinical outcomes following isolated single-or double-level knee osteotomies for patients with variable cartilage defects and extraarticular deformities (10,11,12,13,14,15,16,17,18,19,20,21,22,23,24). More recently, Kim et al 2022 (14) evaluated cartilage regeneration following medial opening wedge high tibial osteotomy (MOWHTO) for medial compartment osteoarthritis (OA) with or without radiographic kissing lesions (RKL).…”
Section: Is An Isolated Knee Osteotomy Sufficient To Treat Patients W...mentioning
confidence: 99%
“…Several authors have reported better macroscopic cartilage regeneration and improved clinical outcomes following isolated single-or double-level knee osteotomies for patients with variable cartilage defects and extraarticular deformities (10,11,12,13,14,15,16,17,18,19,20,21,22,23,24). More recently, Kim et al 2022 (14) evaluated cartilage regeneration following medial opening wedge high tibial osteotomy (MOWHTO) for medial compartment osteoarthritis (OA) with or without radiographic kissing lesions (RKL).…”
Section: Is An Isolated Knee Osteotomy Sufficient To Treat Patients W...mentioning
confidence: 99%
“…In contrast, a greater correction is feasible in CWHTO. The choice between the two techniques was determined preoperatively in accordance with the angular correction, following our institutional guideline [10][11][12]. Specifically, OWHTO was carried out in knees with an angular correction of 15°or less, while CWHTO was chosen for knees with an angular correction exceeding 15°.…”
Section: Surgical Procedures and Postoperative Managementmentioning
confidence: 99%